ANALISIS SENSITIVITAS PAJAK DAN RETRIBUSI DAERAH TERHADAP BELANJA MODAL DAN BELANJANG BARANG DAN JASA DAERAH (Studi Kasus Keuangan Pemerintah Daerah Provinsi Jawa Tengah Periode Tahun 2009-2013) - Rifiana Darmasti, 1352020059; Masdjojo, Gregorius N. (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to analyze and describe the sensitivity of taxes and retribution on capital expenditures and goods and services expenditures. To test the hypothesis, this research used panel data regression with hausman test as a determinant method of the appropriate regression model to be used. Taxes and retribution are the independent variables, while capital expenditures and goods and services expenditures are the dependent variables. The results showed that the capital expenditure only sensitive to retribution while goods and services expenditure sensitive to tax and retribution. Keywords: Tax, Retribution, Capital Expenditures, Goods and Services Expenditures